Effect of Low-Level Laser Therapy on Reversal of Soft Tissue Local Anesthesia in Children: A Randomized Clinical Trial: Laser-assisted recovery from soft tissue anesthesia - Eldehna, Alaa M.; Mohamed, Amira A; Badawy, Sherine; Mostafa, Mohammed H (Journal of Lasers in Medical Sciences, 2025)
Introduction: Prolonged numbness after local dental anesthesia in children can cause significant discomfort, patient anxiety, and risk of accidental lip or cheek injury, limiting normal eating and speaking. Current reversal approaches may require additional injections and risk side effects, underscoring the need for safer alternatives. Recent advances suggest photobiomodulation (PBM) by low-level laser therapy (LLLT) may accelerate recovery, but clinical data in pediatric dentistry remain limited. Methods: In a randomized clinical trial, 20 children with 40 affected teeth were divided into two groups: Group I received anesthesia with 1:100,000 epinephrine, while Group II received 1:200,000 epinephrine. Using a deactivated laser, a split-mouth design was used to compare the laser-treated and control sides. Anesthesia withdrawal was evaluated at 15-minute intervals following patient-reported resolution of numbness. Data were analysed using a paired t-test. Results: Group I showed statistically significant differences from the control in all parameters except chin and cheek numbness. Group II exhibited statistically significant differences in all parameters except chin and cheek numbness resolution and recovery of normal lip sensation. Conclusion: LLLT at 650 nm accelerated anesthesia withdrawal compared to standard conditions, with enhanced effects observed at higher V.C. concentrations. LLLT effectively reduces anesthesia duration by inducing vasodilation and improving blood flow to the irradiated area.